Haploinsufficiency of CSF-1R and clinicopathologic characterization in patients with HDLS - Takuya Konno; Masayoshi Tada; Mari Tada; Akihide Koyama; Hiroaki Nozaki; Yasuo Harigaya; Jin Nishimiya; Akiko Matsunaga; Nobuaki Yoshikura; Kenji Ishihara; Musashi Arakawa; Aiko Isami; et al. (2013)
Objective: To clarify the genetic, clinicopathologic, and neuroimaging characteristics of patients with hereditary diffuse leukoencephalopathy with spheroids (HDLS) with the colony stimulating factor 1 receptor (CSF-1R) mutation. Methods: We performed molecular genetic analysis of CSF-1R in patients with HDLS. Detailed clinical and neuroimaging findings were retrospectively investigated. Five patients were examined neuropathologically. Results: We found 6 different CSF-1R mutations in 7 index patients from unrelated Japanese families. The CSF-1R mutations included 3 novel mutations and 1 known missense mutation at evolutionarily conserved amino acids, and 1 novel splice-site mutation. We identified a novel frameshift mutation. Reverse transcription PCR analysis revealed that the frameshift mutation causes nonsense-mediated mRNA decay by generating a premature stop codon, suggesting that haploinsufficiency of CSF-1R is sufficient to cause HDLS. Western blot analysis revealed that the expression level of CSF-1R in the brain from the patients was lower than from control subjects. The characteristic MRI findings were the involvement of the white matter and thinning of the corpus callosum with signal alteration, and sequential analysis revealed that the white matter lesions and cerebral atrophy relentlessly progressed with disease duration. Spotty calcifications in the white matter were frequently observed by CT. Neuropathologic analysis revealed that microglia in the brains of the patients demonstrated distinct morphology and distribution. Conclusions: These findings suggest that patients with HDLS, irrespective of mutation type in CSF-1R, show characteristic clinical and neuroimaging features, and that perturbation of CSF-1R signaling by haploinsufficiency may play a role in microglial dysfunction leading to the pathogenesis of HDLS.